Comunicaciones ópticas de alta velocidad - Montes Dávila, Walter; Vargas Cuellar, Alexánder (Ingeniería, 1998)
This paper describes the employment of solitons in high-speed optical communications. The solitons are a type of waves characterized fundamentally by the compensation of the linear dispersion of the pulse with its own non-linear compression. The solitons are very appropriate for digital communications at great speed or with a large bandwidth. The propagation of wave-envelope of solitons in optical fibres with no losses can be described by the very well-known non-linear Equation of Schrödinger. Several methods have been developed to solve it, one way is splitting the equation in two parts, one linear and another non-linear; the first one is solved using Fourier transfor m and the other one is solved analytically.